Testing future societies? Developing a framework for test beds and living labs as instruments of innovation governance - Franziska Engels; Alexander Wentland; Sebastian M. Pfotenhauer (Research Policy, 2019)
Test beds and living labs have emerged as a prominent approach to foster innovation across geographical regions and technical domains. They feed on the popular “grand societal challenges” discourse and the growing insight that adequate policy responses to these challenges will require drastic transformations of technology and society alike. Test beds and living labs represent an experimental, co-creative approach to innovation policy that aims to test, demonstrate, and advance new sociotechnical arrangements and associated modes of governance in a model environment under real-world conditions. In this paper, we develop an analytic framework for this distinctive approach to innovation. Our research draws on theories from Science and Technology Studies (STS) and Innovation Studies, as well as in-depth empirical analysis from two case studies – an urban smart energy campus and a rural renewable energy network. Our analysis reveals three characteristic frictions that test beds face: (1) the limits of controlled experimentation due to messy social responses and co-creation activity; (2) a tension between lab-like open-ended experimentation and pressures to demonstrate success; (3) the opposing needs of local socio-cultural specificity and scalability, i.e. the inherent promise of test bed outcomes being generalizable or transferrable because the tested “model society” is presumed to represent a future society at large. These tensions suggest that thinking of test beds as mere technology tests under real-world conditions is insufficient. Rather, test beds both test and re-configure society around a new set of technologies, envisioned futures, and associated modes of governance – occasionally against considerable resistance. By making social order explicitly available for experimentation, test beds tentatively stabilize new socio-technical orders on a local scale in an “as-if” mode of adoption and diffusion. Symmetric attention to the simultaneous co-production of new technical and social orders points to new opportunities and challenges for innovation governance in test-bed settings: Rather than mere enablers of technology, test beds could serve as true societal tests for the desirability of certain transformations. This will require rethinking notions of success and failure, planning with a view towards reversibility, and greater scrutiny of how power is distributed within such settings. Likewise, rather than envisioning test beds as low-regulation zones to drive innovation, they could be strategically deployed to co-develop socially desirable governance frameworks in tandem with emerging technologies in real-time.
Keywords: 330; Innovation governance; Test bed; Living lab; Experimentation; Scaling; Co-production